(untitled) (Journal of the College of Basic Education, 2023)
For students, the university is a new experience that differs from the previous educational experiences that they went through. At the beginning of their university life, students face conditions and problems in various academic, psychological, social and educational fields that require them to pass and agree with them, through an optimistic view of university life, as this is a prerequisite for student success. Their continuity in university studies is considered a guide to general twinning, but the opposite is an indication that there are academic, psychological, social or educational factors or problems that impede their lives.The current research problem emerges in the light of young people’s view of the future, especially university students, and their pessimism about not achieving their goals, aspirations, and future dreams, after the feeling of pessimism and frustration became prevalent among them who are still in the university life stage, causing many social, economic, health problems, and psychological pressures suffered by the youth segment. This is what was reached by the study (Dara, 1995) (Dara, 1995, p. 190) and the study (Al-Kubaisi, 1992) Al-Kubaisi, 1992, p. 3-12). She is exposed to psychological pressures and conflicts that sometimes reach severe crises that lead to behavioral disorders that take multiple forms, including lack of optimism and pessimism in many aspects of life (Al-Hakkak, 2001, p. 2).The problem of the current research is to reveal the level of optimism and pessimism in the university environment and its relationship to specialization and gender.